Application of Data-Driven Decision Making in Education Management in East Kutai Regency - Mustafa, Ivni Alfrisqa; Syamsuddin, Syamsuddin; Ayusaputri, Kusuma Galih; Warman, Warman; Hidayanto, Dwi Nugroho (AS-SABIQUN, 2025)
Data-Driven Decision Making (DDDM) has become one of the most relevant approaches in the era of digitalization. The purpose of this study is to identify the potential and challenges of implementing Data-Driven Decision Making in education management in East Kutai Regency. This study uses a quantitative approach with a correlational descriptive design to analyze the application of Data-Driven Decision Making (DDDM) in education management in East Kutai Regency. This study shows that the implementation of Data-Driven Decision Making (DDDM) significantly increases the effectiveness of education management in East Kutai Regency, especially in overcoming disparities between urban and rural areas. Based on the data, the teacher-student ratio in urban areas is 1:25, while in rural areas it reaches 1:50, indicating the need for redistribution of educators to reduce the gap. In addition, computer access in urban areas reaches 65%, much higher than in rural areas which is only 25%. The availability of textbooks is also better in urban areas (80%) than in rural areas (50%), while parental participation in education is higher in urban areas (75%) than in rural areas (40%). This fact shows the importance of a data-driven approach to support a more equitable allocation of educational resources. The impact of DDDM implementation is also seen in a significant improvement in educational resource managemesnt.